1977
DOI: 10.1073/pnas.74.9.3840
|View full text |Cite
|
Sign up to set email alerts
|

Glucose depletion accounts for the induction of two transformation-sensitive membrane proteinsin Rous sarcoma virus-transformed chick embryo fibroblasts.

Abstract: Chick embryo fibroblasts transformed by Rous sarcoma virus have an increased content of two membrane proteins of molecular weights 78,000 and 95,000. The increased content of the 95,000-dalton protein and the principal increase in the content of the 78,000-dalton protein are not an early consequence of cell transformation but instead are secondary to the rapid depletion of glucose from the growth medium of transformed cells. When glucose is maintained at high levels in the growth medium of transformed cells, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
178
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(187 citation statements)
references
References 19 publications
7
178
0
2
Order By: Relevance
“…After 24 hr of pretreatment with tunicamycin, there was a significant decrease in the fibronectin band, as we had reported previously (3), but the most apparent alterations were the marked increases of two' major polypeptide bands of apparent molecular weights of 95,000 and 75,000 in homogenates of tunicamycin-treated cultures. The electrophoretic mobilities of these bands are identical to those of the "glucose/glycosylation regulated proteins" (GRP) induced in chick cells subjected to glucose starvation or inhibition of glycosylation (23,24).…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…After 24 hr of pretreatment with tunicamycin, there was a significant decrease in the fibronectin band, as we had reported previously (3), but the most apparent alterations were the marked increases of two' major polypeptide bands of apparent molecular weights of 95,000 and 75,000 in homogenates of tunicamycin-treated cultures. The electrophoretic mobilities of these bands are identical to those of the "glucose/glycosylation regulated proteins" (GRP) induced in chick cells subjected to glucose starvation or inhibition of glycosylation (23,24).…”
Section: Methodsmentioning
confidence: 49%
“…Secondary or tertiary CEF were grown for 24 hr in the presence or absence of tunicamycin (0.05 ,4g/ml or 50 nM) in 35-mm plastic tissue culture dishes (Costar) as described (11).…”
Section: Methodsmentioning
confidence: 99%
“…4D). As we and others have shown, the 80-kDa stress protein is synthesized at high levels in cells either deprived of glucose (i.e., it is one of the so-called glucose-regulated proteins) or in cells treated with the calcium ionophore A23187 (9,10,18,25,26). Indirect immunofluorescence studies with a polyclonal antibody raised against the 80-kDa protein have shown the MOL.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory molecule, Grp78, was first discovered in fibroblastic glucose-free cell culture medium [8]. Grp78 is also referred as immunoglobulin binding protein (BiP) [9].…”
Section: Introductionmentioning
confidence: 99%